Regulation of Sodium Channel Activity by Phosphorylation - Scheuer, Todd (2010)
Voltage-gated sodium channels carry the major inward current responsible for action potential depolarization in excitable cells as well as providing additional inward current that modulates overall excitability. Both their expression and function is under tight control of protein phosphorylation by specific kinases and phosphatases and this control is particular to each type of sodium channel. This article examines the impact and mechanism of phosphorylation for isoforms where it has been studied in detail in an attempt to delineate common features as well as differences.